Program for Optimizing the Role of WPA to Reduce the Stigma and Discrimination PLWHA in The Community - Sri Winarni; Wiwin MARTININGSIH (Humanistic Network for Science and Technology (HNST), 2020)
Stigma and discrimination remain significant obstacles in the management of HIV / AIDS prevention programs. The data shows there are stigma and discrimination within the health service, treatment is not going well. PLWHA tends to be ashamed and afraid to control or get medicine in the hospital, injustice to the provision of services, thus, low quality of care, and lack of respect for patients. The purpose of this study was to reduce the stigma and discrimination of HIV / AIDS patients in the community, through community empowerment programs. Long-term benefits were finding the right design to reduce stigma and discrimination toward HIV / AIDS patients, through community empowerment by integrating the concepts of social support, social networks, and social marketing. One group pretest-posttest design was used in this research. Seventy-five respondents were taken purposively. The intervention was